HUBUNGAN PENGETAHUAN DAN PERSEPSI DENGAN SIKAP PENERIMAAN VAKSIN COVID-19 PADA IBU HAMIL DI PUSKESMAS BANGKONOL PANDEGLANG - Diana Agustina (2022)
Background : COVID-19 was declared global pandemic by WHO. One of the vulnerable populations at risk of contracting COVID-19 is pregnant women. Vaccines are considered as way to maintain the immune system. But in giving vaccines there are pros and cons. Several factors can influence vaccine acceptance include perceptions of disease risk, trust the health care system, knowledge and perceptions about vaccine safety and efficacy. Purpose : Determine the relationship between knowledge and perceptions about COVID-19 vaccination with the attitude receiving COVID-19 vaccine in pregnant women at Puskesmas Bangkonol Pandeglang. Methode : Descriptive analytic with a cross sectional design. The sampling technique used consecutive sampling with 126 samples. The research instrument used the Knowledge COVID-19 Vaccine, Perception COVID-19 Vaccine and Attitudes COVID-19 Vaccine. Result : There is no relationship between knowledge and attitude receiving COVID-19 vaccine (p value 0,806) and there was a relationship between perception and attitude receiving COVID-19 vaccine (p value 0,005). Conclusion : There is no relationship between knowledge and attitude receiving COVID-19 vaccine, but there is relationship between perception and attitude receiving COVID-19 vaccine. Suggestion : The puskesmas can make programs such as peer group support to change the perception pregnant women about COVID-19 vaccine.